Endovascular treatment of aneurysms of the paraophthalmic segment of the internal carotid artery: Current status - Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2022)
The paraophthalmic segment of the internal carotid artery (ICA) originates from the distal border of the cavernous ICA and terminates at the posterior communicating artery. Aneurysms arising from the paraophthalmic segment represent 5–10% of intradural aneurysms. Due to the advent of endovascular treatment (EVT) techniques, specifically flow-diverting stents (FDSs), EVT has become a good option for these aneurysms. A literature review on EVT for paraophthalmic segment aneurysms is necessary. In this review, we discuss the anatomy of the paraophthalmic segment, classification of the paraophthalmic segment aneurysms, EVT principle and techniques, and prognosis and complications. EVT techniques for paraophthalmic segment aneurysms include coil embolization, FDSs, covered stents, and Woven EndoBridge devices. Currently, coiling embolization remains the best choice for ruptured paraophthalmic segment aneurysms, especially to avoid long-term antiplatelet therapy for young patients. Due to the excessive use of antiplatelet therapy, unruptured paraophthalmic segment aneurysms that are easy to coil should not be treated with FDS. FDS is appropriate for uncoilable or failed aneurysms. Other devices cannot act as the primary choice but can be useful auxiliary tools. Both coiling embolization and FDS deployment can result in a good prognosis for paraophthalmic segment aneurysms. The overall complication rate is low. Therefore, EVT offers promising treatments for paraophthalmic segment aneurysms. In addition, surgical clipping continues to be a good choice for paraophthalmic segment aneurysms in the endovascular era.